Apparent digestibility of selected feed ingredients for Nile tilapia (Oreochromis niloticus) - Köprücü, K; Özdemir, Y (Elsevier, 2005)
In this study, apparent digestibility coefficients (ADCs) of nutrients and energy in selected feed ingredients were determined for Nile tilapia. ADCs were determined using a reference diet with chromic oxide indicator and test diets that contained 70% reference diet, by weight, and 30% of the test ingredient being evaluated. Fish were fed twice daily at the rate of 4% of their body weight at 27+/-1 degrees C of water temperature. Fecal samples were collected from three replicate groups of fish using fecal collection column attached to fish rearing aquaria. The ADCs of the anchovy meal, corn gluten meal, soybean meal, gammarid meal and crayfish exoskeleton meal were: dry matter, 91.6%, 93.2%, 90.9%, 77.0%, and 75.7%; protein, 90.5%, 89.0%, 87.4%, 75.8% and 71.0%; lipid, 97.5%, 94.0%, 92.1%, 75.8%, and 72.0%; fiber or chitin, 90.1%, 96.1%, 95.2%, 71.5%, and 69.3%; ash, 38.1%, 74.9%, 71.6%, 32.4%, and 30.8%; calcium, 17.1%, 20.3%, 20.9%, 13.2%, and 11.6%; phosphorus, 27.8%, 28.2%, 30.1%, 10.5%, and 9.7%; nitrogen-free extract 93.7%, 95.8%, 92.6%, 84.2%, and 82.7%; energy, 92.1%, 89.0%, 83.7%, 65.6%, and, 54.8%; and average amino acid, 91.2%, 89.6%, 87.1%, 76.2%, and 70.6%, respectively. These values were significantly affected by test ingredients (P<0.05). The results of the study suggest that the ADCs of protein are indicative of amino acid digestibility. However, variation in individual amino acid digestibility between feed ingredients means that determination of this parameter may allow more accurate and economical feed formulation. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Nile tilapia; apparent digestibility; feed ingredients; nutrients; energy